Features of Surgical Treatment of Neovascular Glaucoma - Jamshedovich, Ismoilov Jasur (American Journal of Bioscience and Clinical Integrity, 2025)
Treatment of glaucoma has a pathogenetic focus and includes: reducing IOP to a tolerable (target) level; correction of metabolic disorders; use of cyto- and neuroprotectors to preserve cells in the anterior segment of the eye and (especially) the retina; treatment of concomitant diseases that negatively affect the course of the glaucomatous process. The leading role in the treatment of glaucoma belongs to reducing IOP. Currently, three main methods of hypotensive treatment are used: drug, laser and surgical. Modern ophthalmic hypotensive agents include miotics, adrenergic agonists (adrenaline and α 2 -adrenergic stimulators), (β-blockers, carbonic anhydrase inhibitors, some prostaglandins, agents that have an osmotic effect. The mechanism of their action on IOP is associated with improving the remorphological, remorphological outflow of the eye), secretion of intraocular fluid (α 2 -adrenergic agonists, (β-blockers, carbonic anhydrase inhibitors).